PENGARUH MODEL SOMATIC, AUDITORY, VISULA DAN INTELLECTUAL (SAVI) TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPAS MATERI SIKLUS AIR - Br PA, Rita Herlina; Togatorop, Jainal; Bangun, Angelika Kristin Br (Jurnal Ilmiah Aquinas, 2025)
This study aims to determine the effect of the use of the Somatic, Auditory, Visual, Intellectual (SAVI) model on student learning outcomes in the subject of science on the water cycle material of grade V students of SDN 105308 Namo Bintang. The method used in this study is a quantitative method with a one-group pretest-posttest Design. And the instrument used in the study was a learning outcome test designed to measure student learning outcomes before and after the application of the Somatic, Auditory, Visual, Intellectual (SAVI) model. This study used a sample class with 30 students. Based on the results of the study, the student learning outcomes before using the Somatic, Auditory, Visual, Intellectual (SAVI) model were an average of 53.27. After using the Somatic, Auditory, Visual, Intellectual (SAVI) model, an average value of 84.86 was obtained, including high criteria. Based on the results of the hypothesis test, the Tcount value = 19.19 and the TTable value = 2.01. Based on these data, Tcount> TTable where H1 is accepted and Ho is rejected. So it can be concluded that there is an influence of the use of the Somatic, Auditory, Visual, Intellectual (SAVI) model on the learning outcomes of students in the subject of science learning on the water cycle material of class V students at SDN 105308 Namo Bintang..